CREATING AN ADMIN PANEL IN WORDPRESS (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This research paper explores the process of creating a custom admin panel in WordPress, focusing on the technical aspects and best practices to enhance the functionality and user experience. WordPress, as a content management system (CMS), provides a default admin panel; however, custom requirements often necessitate the development of a tailored interface to meet specific needs. This paper discusses the steps involved in creating a custom admin panel, the importance of user roles and capabilities, and the integration of custom post types and taxonomies. The paper concludes with a discussion on the security considerations and the potential for scalability in WordPress admin panel development.